Enhanced Lithium Storage Performance in Si/MXene Porous Composites - Hao Yang; Tingting Jiang; Yingke Zhou (Inorganics, 2023)
As a potential negative electrode material for lithium-ion batteries (LIBs), silicon has a relatively high specific lithium storage capacity. However, the large volume change during the cycle may result in the isolation with the current collector and therefore the rapid capacity decay during cycling. The poor electric conductivity of the silicon limits the high-power density application in LIBs. To meet the above challenges, a stable Si/Ti3C2Tx composite material was designed. Si nanoparticles are bonded with -NH2 group so that the silicon surface has a positive charge, which can then be electrostatic self-assembly with negatively charged MXene nanosheets in a facile freeze-drying method. Silicon nanoparticles were anchored on the surface or inside the interspace of the MXene nanosheets, which could improve the conductivity of the composites. The composite material (NH2-Si/MXene) presented a stable and porous structure with extra room for silicon expansion and plentiful channels for carrier transportation. Benefiting from the improved structural stability and enhanced charge storage dynamics, the discharge capacity of NH2-Si/MXene is 1203.3 mAh g−1 after 100 cycles at 200 mA g−1. These results provide new insights for the application of silicon-based negative electrode materials in high-energy-density LIBs.